Justice - Watson, Lawrence (Minneapolis : Milkweed Editions, 1995)
The story of the Hayden family in Montana, where their word seemed to be the law from 1899 to 1937.
Booklist starred.
Library Journal Starred.
School Library Journal.
Adult.
Adult
Keywords: Family -- Montana -- Fiction; Sheriffs -- Montana -- Fiction; Family -- Montana -- Fiction; Sheriffs -- Fiction; Montana -- Fiction; Montana -- Fiction; Domestic fiction; Historical fiction